Nitrooleic Acid Attenuates Lipid Metabolic Disorders and Liver Steatosis in DOCA-Salt Hypertensive Mice. (11th March 2015) - Wang, Haiping; Sun, Jing; Jia, Zhanjun; Yang, Tianxin; Xu, Liang; Zhao, Bing; Yu, Kezhou; Wang, Rong
Abstract : Nitrooleic acid (OA-NO2 ) is endogenous ligands for peroxisome proliferator-activated receptors. The present study was aimed at investigating the beneficial effects of OA-NO2 on the lipid metabolism and liver steatosis in deoxycorticosterone acetate- (DOCA-) salt induced hypertensive mice model. Male C57BL/6 mice were divided to receive DOCA-salt plus OA-NO2 or DOCA-salt plus vehicle and another group received neither DOCA-salt nor OA-NO2 (control group). After 3-week treatment with DOCA-salt plus 1% sodium chloride in drinking fluid, the hypertension was noted; however, OA-NO2 had no effect on the hypertension. In DOCA-salt treated mice, the plasma triglyceride and total cholesterol levels were significantly increased compared to control mice, and pretreatment with OA-NO2 significantly reduced these parameters. Further, the histopathology of liver exhibited more lipid distribution together with more serious micro- and macrovesicular steatosis after DOCA-salt treatment and that was consistent with liver tissue triglyceride and nonesterified fatty acids (NEFA) content. The mice pretreated with OA-NO2 showed reduced liver damage accompanied with low liver lipid content. Moreover, the liver TBARS, together with the expressions of gp91phox and p47phox, were parallelly decreased. These findings indicated that OA-NO2 had the protective effect on liver injury against DOCA-salt administration and the beneficial effect could be attributed to its antihyperlipidemic activities.